Semiotic Analysis Of “Ruang Guru” Application Advertisement - Putri Dilasari (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2022)
This study deals with Semiotic Analysis of Ruang Guru Application Advertisement. . The objectives of this research were to find out the types of semiotic sign and the interpretation of signs used by Ruang Guru Application in the online posters advertisement. In this research used descriptive qualitative methods. 5 online posters advertisement were taken in the poster of Ruang Guru Application. In collecting the data, all posters were taken by searching through the international network services to get words, pictures, symbols that coded semiotic signs in Ruang Guru Poster. The steps of collecting the data were searching the posters, selecting the posters, classifying semiotic signs in the posters were chosen, and collecting all the signs in 5 posters. This research was suggested for the future researchers who want to conduct the research about semiotic signs. Moreover, the students of English Department were recommended to read this research to comprehend and improve the knowledge about semiotics. All semiotic signs were analyzed based on type of semiotics proposed by Charles Sanders Peirce, such as Icon, Index and Symbol. After analyzing the data, 49 types of semiotic signs are found. There were 11 Icons, 14 Indexes and 25 Symbols in the 5 poster advertisement of Ruang Guru Application.